Pelatihan Pembuatan Media Pembelajaran Digital Berbasis Game Interaktif Menggunakan Wordwall Bagi Guru SD Kreatif Insan Rabbani - Wahjudi, Eko; Wibowo, Sapto; Hardini, Han Tantri (Universitas Negeri Surabaya, 2024)
This service activity was carried out at Insan Rabbani Creative Elementary School Jl. KRI P Rupat No. 70, Pager, Sawotratep, Gedangan, Sidoarjo, East Java. Based on the situation analysis of the partners, the main problem lies in teachers who have difficulty in developing creative and innovative digital learning media due to lack of understanding and skills. Therefore, this activity is a solution to the problem that can be overcome by providing training for teachers to develop interactive game-based digital learning media using the wordwall platform. The purpose of this activity is to encourage teachers at Insan Rabbani Creative Elementary School to be more innovative, especially in organizing learning activities through the development of digital learning media so that the hope is to improve the quality of learning. The methods used in this community service activity are field surveys, demonstrations, lectures, practices, discussions and distributing questionnaires. This PKM activity has been successful and running well, which is indicated by the results of the participant survey getting a percentage of 83.95% which means that it has received a